40Ar–39Ar dating of pseudotachylytes: the effect of clast–hosted extraneous argon in Cenozoic fault–generated friction melts from the West Antarctic Rift System - DI VINCENZO G.; ROCCHI S.; ROSSETTI F.; STORTI, Fabrizio (2004)
Fault-generated pseudotachylytes are the product of frictional melting during high-velocity slip associated with coseismic faulting. 40Ar–39Ar dating of pseudotachylytes represents a powerful tool to directly determine the age of brittle faulting which is otherwise dated only indirectly. However, the pronounced spatial heterogeneity of most endogenically generated pseudotachylytes, due to the intimate coexistence of unmelted mineral clasts from the source rock, frictional glass and neogenic igneous minerals, often precludes a straightforward interpretation of argon data. This requires careful evaluation of the role of clasts in plaguing the age record of the pseudotachylyte matrix. This study exploits the full potential of the 40Ar–39Ar method, using laser step-heating and laser in situ techniques in conjunction with textural and chemical characterisation at the microscale to disentangle the complexity of the first record of pseudotachylytes generated in the right-lateral fault systems which dissect the western shoulder of the West Antarctic Rift System. Pseudotachylytes occur as fault and injection veins. They exhibit glassy matrices with a potassium feldspar-like composition, and invariably contain, at a millimeter to microscopic scale, unmelted quartz and subordinate feldspars from the source rock. Injection veins characteristically contain much fewer mineral clasts. In situ ultraviolet (UV) laser analyses indicate that quartz from the host rock and from clasts within the fault veins contains significant amounts (f10–50 ppb) of parentless 40Ar, most probably hosted in microscopic to submicroscopic fluid inclusions, associated with high Cl/K ratios. Infrared laser step-heating experiments on fault vein pseudotachylyte matrices yield strongly discordant age spectra with an overall saddle shape characterised by a minimum at f34 Ma, unrealistically old ages at high temperatures associated with high Cl/K ratios and total gas ages of 41.5–44.3 Ma. Petrographic data and the pronounced compositional similarity ...